Seed and seedling predation by vertebrates mediates the effects of adult trees in two temperate tree species - Holík, Jan; Janík, David (Oecologia, 2022)
Specialised natural enemies can locally suppress seeds and seedlings near conspecific adults more than far from them. Whilst this is thought to facilitate species coexistence, the relative contribution of multiple enemies to whether heterospecific seeds and seedlings rather than conspecifics perform better beneath a particular adult species remains less clear, especially in regions with spatially extensive monodominant stands. We designed a field exclusion experiment to separate the effects of fungi, insects and vertebrates on the seedling establishment and early survival of two temperate tree species, Fagus sylvatica and Picea abies, in the adult tree monocultures of these species. Our experiment demonstrates the key role of vertebrates in mediating the effects of adult trees on seeds and seedlings. Due to vertebrates and partly insects, Fagus sylvatica seedlings survived worse beneath conspecific than heterospecific adults and were also outperformed by Picea abies seedlings beneath their own adults. Picea abies seedling establishment was higher beneath conspecific than heterospecific adults, but Fagus sylvatica seedlings outperformed them beneath their own adults. The impact of enemies on Picea abies establishment beneath conspecific adults was less clear. Fungi did not influence seedling establishment and survival. Our findings highlight the need to compare enemy impacts on each seedling species beneath conspecific and heterospecific adults with their impacts on conspecific and heterospecific seedlings beneath a particular adult species. Such evaluations can shed more light on the role of enemies in tree communities by identifying the plant-enemy interactions that facilitate species coexistence and those that promote species monodominance.
Keywords: Animals; Species coexistence; Plant–enemy interactions; houby; Seeds; semena rostlinná; Predatory Behavior; Seedling establishment; Natural enemies; Seedling survival; stromy; Fungi; hmyz; Monodominance; Vertebrates; obratlovci; predátorské chování; zvířata; semenáček; Seedlings; Trees; Insecta